2016
DOI: 10.1177/2048004016669645
|View full text |Cite
|
Sign up to set email alerts
|

Association of glutathione S-transferase GSTM1 and GSTT1 deletion polymorphisms with obesity and their relationship with body mass index, lipoprotein and hypertension among young age Saudis

Abstract: ObjectivesPersistent oxidative stress is one of the several risk factors that may be associated with the etiology of obesity. The present study is aimed to investigate association between GSTM1 and GSTT1 polymorphisms with obesity and their relationship with plasma lipoproteins, body mass index (BMI) and hypertension.DesignThe GSTM1 and GSTT1 deletion polymorphisms were analyzed by multiplex polymerase chain reaction. The lipoproteins were measured in plasma using commercially available kit and the weight, hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…There is not a lot of study about these association, while Almoshabek and al. reported in young age Saudis that frequencies of GSTM1-active/GSTT1-null (OR = 2.70; p < 0.001) and GSTM1-null/GSTT1-null (OR = 2.43, p = 0.018) were significantly higher in overweight/obese as compared to normal weight [55]. Our results are in accordance with those of Afrand and al.…”
Section: Discussionsupporting
confidence: 92%
“…There is not a lot of study about these association, while Almoshabek and al. reported in young age Saudis that frequencies of GSTM1-active/GSTT1-null (OR = 2.70; p < 0.001) and GSTM1-null/GSTT1-null (OR = 2.43, p = 0.018) were significantly higher in overweight/obese as compared to normal weight [55]. Our results are in accordance with those of Afrand and al.…”
Section: Discussionsupporting
confidence: 92%
“…It is important to note that there is a lack of information regarding these genotypes among children with obesity. However, studies in adults suggest that the null genotype of GST-M and GST-T may be associated with a higher risk of obesity 26,32,33 . Results of the current study revealed a signi cant deviation from Hardy-Weinberg proportion in GST-M and GST-T genotype distributions among children who suffer from obesity, with relatively higher null genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…But none of these provides a precise explanation of the process that underlies obesity. The significance of genetics in obesity has been clearly shown by research on ethnic prevalence, family aggregation, twins, and adoption [1,2]. The etiopathology of obesity has been linked to several risk factors, including both genetic and environmental ones [3,4].…”
Section: Introductionmentioning
confidence: 99%